Elemene Injection Overcomes Paclitaxel Resistance in Breast Cancer through AR/RUNX1 Signal: Network Pharmacology and Experimental Validation - Gu, Xidong; Xu, Leilai; Fu, Yuanyuan; Fan, Shuyao; Huang, Tianjian; Yu, Jiangting; Chen, Jiaying; Sui, Xinbing; Xie, Xiaohong (Current Pharmaceutical Design, 2024)
Background: Paclitaxel (PTX) is a cornerstone chemotherapy for Breast Cancer (BC), yet its impact is limited by emerging resistance. Elemene Injection (EI) has shown potential in overcoming chemotherapy resistance. However, the efficacy by which EI restores PTX sensitivity in BC and the implicated molecular mechanism remain uncharted. Methods: Network pharmacology and bioinformatic analysis were conducted to investigate the targets and mechanisms of EI in overcoming PTX resistance. A paclitaxel-resistant MCF-7 cell line (MCF-7PR) was established. The efficacy of EI and/or PTX in inhibiting cell viability was evaluated using sulforhodamine B assay, while cell proliferation was assessed using EdU staining. Furthermore, protein and gene expression analysis was performed through Western blotting and qPCR. Results: The EI containing three active components exhibited a multifaceted impact by targeting an extensive repertoire of 122 potential molecular targets. By intersecting with 761 differentially expressed genes, we successfully identified 9 genes that displayed a direct association with resistance to PTX in BC, presenting promising potential as therapeutic targets for the EI to effectively counteract PTX resistance. Enrichment analysis indicated a significant correlation between these identified targets and critical biological processes, particularly DNA damage response and cell cycle regulation. This correlation was further substantiated through meticulous analysis of single-cell datasets. Molecular docking analysis revealed robust binding affinities between the active components of the EI and the identified molecular targets. Subsequently, in vitro experiments unequivocally demonstrated the dose- and time-dependent inhibitory effects of the EI on both PTX-resistant and sensitive BC cell lines, effectively mitigating the resistance phenotype associated with PTX administration. Furthermore, our findings have indicated EI to effectively suppress the protein expression levels of AR and RUNX1 in MCF-7 and MCF-7PR cells under PTX treatment, as well as downregulate the mRNA expression levels of stem-like properties' markers, KLF4 and OCT4, in these cell lines. Conclusion: Elemene Injection (EI) application has exhibited a significant capability to mitigate PTX resistance in BC, which has been achieved through targeted suppression of the AR/RUNX1 axis, revealing a key strategy to overcome chemotherapeutic resistance.
Keywords: elemene injection